Dynamics of boron-10 burning out in the control rods of reactivity of the WWR-K reactor - Sairanbayev, D.S.; Koltochnik, S.N.; Shaimerdenov, A.A.; Kenzhin, Y.A.; Almagambetov, A.N.; Tsuchiya, K. (Recent Contributions to Physics, 2019)
In 2015, as part of the conversion of the WWR-K reactor to low enrichment fuel, the main reactor systems were modernized, including the complete replacement of the reactor control and protection system (CPS). The energy intensity in the new, more compact core has become noticeably higher, the number and geometric parameters of the working bodies (WB) of the CPS have changed. Boron carbide with a natural isotopic composition is used as the material of the absorber in the CPS WB. CPS WB are responsible for managing the nuclear fission chain reaction of uranium. The WWR-K reactor is a stationary research reactor, so for its operation it is necessary to create an initial reactivity margin. At the beginning of the reactor operating cycle, most of the CPS rod is immersed in the core. During the operation of the reactor, the rod is gradually removed from the core due to the "poisoning" of the core and the burning of uranium. A nuclear reaction proceeds on the boron-10 isotope with absorption of a thermal neutron and the formation of an alpha particle and a lithium-7 isotope, which leads to a decrease in the nuclei of the initial isotope, i.e. burnout of boron-10. A decrease in the mass of the boron-10 isotope in the CPS rod will lead to a decrease in its physical efficiency, which directly affects the nuclear safety of the reactor. An important criterion for the operation of a nuclear reactor is the creation of subcriticality of the core for the safe shutdown of a nuclear chain reaction. The subcriticality of the core depends on the total efficiency of the reactivity compensation rods. In this work, a quantitative assessment of the burnup of boron-10 in the WB of the WWR-K reactor is presented. The effect of burnout of the boron-10 isotope on the physical efficiency of CPS rods during their long-term operation in the core of the WWR-K reactor is shown. The time intervals of 1, 3 and 10 years are considered. The obtained results can be used to justify the resource and safety of operation of the control and safety rods of the WWR-K reactor. The calculations were performed using the MNCP6 software with the library of nuclear constants ENDF/B-VII.1.